Sustainable investing in times of crisis: Evidence from bond holdings and the COVID-19 pandemic - Fatica, Serena; Panzica, Roberto (Journal of Banking & Finance, 2024)
We examine the resilience of green bonds to the COVID-19 shock through the lens of institutional investors’ holdings. We show that the green label has a positive impact on bond holdings both in normal times and during the COVID crisis. Moreover, during the pandemic outbreak, green bonds experienced lower net sales, on average, than equivalent conventional bonds, while no significant differences emerge in normal times. The results hold across different investor classes, including mutual funds exposed to large outflows, and are not driven by issuers’ fundamentals. We also document that the ownership of green fixed income securities is more concentrated than that of comparable conventional bonds, and that concentration has increased in the first quarter of 2020. JEL Classification: G01, G11, G23